Sistema de controle aplicado à automação de irrigação agrícola - Reis, Jéssica Sarto dos (2015)
The agricultural sector accounts for about 72% of the total freshwater consumption in Brazil and much of the irrigation systems have no control of water use for this activity. The present work aims at presenting the results obtained from the development of an electronic controller for use in irrigation systems using the method of irrigation spray. This control allows a saving of electricity, water and hand labor, increasing the quality of the irrigation system. This control will occur by the soil moisture monitoring by a moisture sensor, and monitoring of the incidence of light, to know whether it is day or night, by a light sensor, using for processing such data a development board Arduino Uno. In principle the whole structure has been validated, including the components defined for use in the system. The economic viability of the project has also been proven due to low investment cost, as to be insignificant before the obtained energy saving and water and the quality of the irrigation process.